Washable anti-wrinkle fabric and preparation method thereof
By reacting the modified cotton fabric and nano titanium dioxide, combined with the finishing of specific chemicals, a water-resistant and wrinkle-resistant fabric is prepared, which solves the problems of ultraviolet protection, flammability, and weakening of the functions of cotton fabrics in outdoor use, realizing the fabric multiple performance improvements.
Patent Information
- Application Number
- CN202411611772.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Cotton fabrics cannot effectively protect against ultraviolet rays when used outdoors, and are prone to aging and fading. They are also flammable and weakened after cleaning, making it difficult to meet the needs of anti-ultraviolet, flame retardant and wrinkle.
Wash-resistant and wrinkle-resistant fabrics are prepared by reaction of modified cotton fabrics and modified nanotitanium dioxide. By pretreatment of cotton fabrics, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol, nanotitanium dioxide wrapped in chitosan and Para-hydroxybenzaldehyde, followed by 1-chloromethyl-3-trifluoromethylbenzene, to form a fabric with flame retardant, antibacterial and UV resistance.
It achieves the improvement of the fabric's wash resistance, wrinkle resistance, flame retardant and UV resistance, extends the service life of the function and reduces safety risks.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a washable and wrinkle-resistant fabric and a preparation method thereof. Background Art
[0002] Cotton fabric is deeply loved by users because of its comfort and softness. Although cotton fabric is breathable and comfortable, it cannot effectively protect against ultraviolet rays. When exposed to the sun for a long time, it not only provides insufficient protection for human skin, but also accelerates the aging and fading of the fabric itself, which limits its application in outdoor clothing. In addition, natural cotton fabric is extremely flammable, increasing the safety risks when wearing it; cotton fabric is very prone to wrinkles when subjected to external forces, which increases the inconvenience and time cost of daily maintenance. Therefore, the preparation of fabrics with anti-UV, flame retardant and anti-wrinkle properties can broaden the application areas of cotton fabrics.
[0003] There are also some fabrics with anti-ultraviolet and flame-retardant functions in the prior art, but these functions will gradually weaken after repeated washing, so it is necessary to invent a functional fabric that is washable. The washable and wrinkle-resistant cotton fabric prepared by the present invention not only has excellent anti-ultraviolet and flame-retardant properties but also has certain washable and wrinkle-resistant properties. Summary of the invention
[0004] The object of the present invention is to provide a washable and wrinkle-resistant fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A washable and wrinkle-resistant fabric is prepared by reacting modified cotton fabric with modified nano titanium dioxide to obtain modified cotton grey cloth, and then post-finishing with 1-chloromethyl-3-trifluoromethylbenzene.
[0006] As an optimization, the modified cotton fabric is prepared by reacting pretreated cotton fabric, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol.
[0007] As an optimization, the modified nano titanium dioxide is prepared by reacting nano titanium dioxide wrapped by chitosan and p-hydroxybenzaldehyde.
[0008] A method for preparing a washable and wrinkle-resistant fabric comprises the following steps: (1) The pretreated cotton fabric is immersed in a phosphite solution for 15-20 minutes, and the wet weight is controlled to be 198%-202% after rolling, and heated at 180°C for 5 minutes, washed with pure water, and dried at 100°C for 1-2 hours, and then immersed in a 4-amino-3-nitrobenzyl alcohol solution for 15-20 minutes, and the wet weight is controlled to be 198%-202% after rolling, and heated at 180°C for 5 minutes, and washed with pure water 3-4 times, and dried at 100°C for 1-2 hours to obtain a modified cotton fabric; (2) Mix the chitosan-coated nano-titanium dioxide and anhydrous ethanol at a mass ratio of 1:50-60, ultrasonicate at 20-40kHz for 10-20min, add p-hydroxybenzaldehyde 2-3 times the mass of the chitosan-coated nano-titanium dioxide, adjust the pH to 4-5 with a 0.5mol / L sodium hydroxide aqueous solution, heat to 60-80°C, stir and reflux for 3-4h, filter and wash with anhydrous ethanol for 3-4 times, and dry at 60°C for 6-8h to obtain functionalized nano-titanium dioxide; (3) The modified cotton fabric is immersed in a 6wt% hydrochloric acid aqueous solution for 10-20 minutes, and the wet weight is controlled to be 120%-140% after rolling. The fabric is reacted at 25-30°C for 10-20 minutes, washed with anhydrous ethanol for 3-4 times, dried at 60°C for 6-8 hours, and then immersed in a 0.5g / mL sodium nitrite aqueous solution for 10-15 minutes. The wet weight is controlled to be 90%-110% after rolling, washed with pure water for 4-5 times, and dried at 100°C for 1-2 hours to obtain a diazotized cotton fabric; (4) Modified nano titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:50-60, ultrasonicated at 20-40kHz for 10-20min, 13wt% sodium carbonate aqueous solution was added to adjust the pH to 8-9, diazotized cotton fabric was added for immersion, wet weight was controlled to 60%-80% after rolling, reacted at 25-30℃ for 1-2h, washed with pure water for 4-5 times, dried at 100℃ for 1-2h, and then immersed in sodium hydroxide. 5-10 minutes in ethanol solution, after rolling, the wet weight is controlled to be 100%-120%, reacted at 50-60°C for 20-30 minutes, washed with pure water for 4-5 times, dried at 100°C for 1-2 hours, immersed in glucose solution, after rolling, the wet weight is controlled to be 110%-120%, reacted at 50-60°C for 20-30 minutes, washed with pure water for 4-5 times, dried at 100°C for 1-2 hours, and obtained grey cloth; (5) 1-chloromethyl-3-trifluoromethyl is prepared into a finishing agent solution of 60-80 g / L with anhydrous ethanol, triethylamine is added in an amount of 0.2-0.3 times the mass of 1-chloromethyl-3-trifluoromethyl, and the solution is added to the grey fabric, wherein the mass ratio of the grey fabric to the finishing solution is 1:20-30. After immersion for 60-90 min, the solution is subjected to a one-immersion-one-rolling process, pre-baked at 60-80°C for 2 min, and then heated to 150-180°C and baked for 2-5 min to obtain the fabric.
[0009] As an optimization, the preparation method of the pretreated cotton fabric in step (1) is: immersing the cotton fabric in a 0.2wt% sodium dodecyl sulfate aqueous solution and ultrasonicating for 5-10 minutes, the ultrasonic frequency is 20-40kHz, the warp and weft density of the cotton fabric is 150*100 strands / 10cm, and the surface density is 108g / cm 2 , then immersed in anhydrous ethanol for 5-10 minutes, the ultrasonic frequency is 20-40kHz, washed with pure water for 3-4 times, and dried in an oven at 80-90℃ for 1-2h to obtain the pretreated cotton fabric.
[0010] As an optimization, the phosphite solution in step (1) is prepared by mixing phosphite and anhydrous ethanol, wherein the mass ratio of phosphite to anhydrous ethanol is 1:12-15, and the 4-amino-3-nitrobenzyl alcohol solution is prepared by mixing 4-amino-3-nitrobenzyl alcohol and anhydrous ethanol, wherein the mass ratio of 4-amino-3-nitrobenzyl alcohol to anhydrous ethanol is 1:7-8.
[0011] As an optimization, the preparation method of chitosan-coated nano-titanium dioxide in step (2) is as follows: chitosan and acetic acid aqueous solution are uniformly mixed in a mass ratio of 1:4-5, the volume ratio of acetic acid to pure water in the acetic acid aqueous solution is 1:30-40, 20-30 times the mass of the chitosan solution of nano-titanium dioxide is added, ultrasonication is performed at 20-40 kHz for 30-40 min, 0.5 times the mass of the acetic acid aqueous solution of 20wt% ammonia water is added, the mixture is allowed to stand for 30-40 min, the mixture is filtered and washed with pure water for 6-8 times, and the mixture is dried at 60°C for 2-3 h to obtain chitosan-coated nano-titanium dioxide.
[0012] As an optimization, the sodium hydroxide ethanol solution in step (4) is formed by mixing sodium hydroxide, pure water and anhydrous ethanol, wherein the mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5; the glucose solution is formed by mixing glucose and pure water, wherein the mass ratio of glucose to pure water is 1:2.5-3.
[0013] As an optimization, the one-immersion-one-rolling process in step (5) is as follows: the immersion-rolling temperature is 20-50° C., and the rolling rate is 100%-120%.
[0014] As an optimization, the nano titanium dioxide model is T5, purchased from Beijing Dekedaojin Technology Co., Ltd.
[0015] As an optimization, the diazotized cotton fabric in step (3) and step (4) is prepared by diazotizing the nitroaniline structure on the surface of the cotton fabric to form a salt, and then reacting with the phenol structure on the surface of the nano-titanium dioxide. The reaction process is shown in the figure below:
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the washable and wrinkle-resistant fabric, the present invention firstly reacts pretreated cotton fabric, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol to obtain modified cotton fabric, then reacts nano titanium dioxide wrapped in chitosan and p-hydroxybenzaldehyde to obtain modified nano titanium dioxide, then reacts the modified cotton fabric and the modified nano titanium dioxide to obtain modified cotton grey cloth, and then uses 1-chloromethyl-3-trifluoromethylbenzene for post-finishing to obtain the washable and wrinkle-resistant fabric.
[0017] Firstly, pretreated cotton fabric, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol are reacted to obtain modified cotton fabric, the pretreated cotton fabric and triethyl phosphite are subjected to ester exchange reaction, a structure having flame retardant properties is grafted onto the cotton fabric to give the fabric flame retardant properties, and then 4-amino-3-nitrobenzyl alcohol is used to introduce a nitroaniline structure into the cotton fabric through an ester exchange reaction, and subsequent reactions can be carried out.
[0018] Secondly, nano-titanium dioxide has a high refractive index and can not only reflect ultraviolet rays but also absorb ultraviolet rays, which can give the fabric good anti-ultraviolet properties. The outer layer of nano-titanium dioxide is wrapped with antibacterial chitosan, which can give the fabric excellent antibacterial properties. The amino group on chitosan can form a Schiff base with the aldehyde group on p-hydroxybenzaldehyde, and introduce a phenolic hydroxyl structure on the surface of nano-titanium dioxide, which can carry out subsequent reactions. Finally, the modified cotton fabric and modified nano-titanium dioxide are reacted to obtain modified cotton grey cloth, and then 1-chloromethyl-3-trifluoromethylbenzene is used for post-finishing to obtain washable and wrinkle-resistant fabric; the nitroaniline structure on the modified cotton fabric is diazotized to form a salt, which can be coupled with the phenolic hydroxyl structure on the surface of nano-titanium dioxide, and then reduced by glucose to finally form a benzotriazole structure. The benzotriazole structure is based on the phenolic-quinone tautomer that converts the absorbed light energy into heat energy to achieve the effect of absorbing ultraviolet rays and further improve the anti-ultraviolet performance of the fabric. Finally, 1-chloromethyl-3-trifluoromethylbenzene is used for finishing to react with the excess phenolic hydroxyl structure on the surface of nano-titanium dioxide, reduce the excess active groups on the surface of the fabric, and improve the anti-wrinkle performance of the fabric. The introduction of fluoromethyl can also further improve the flame retardant properties of the fabric. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] The cotton fabrics used in the following examples and comparative examples were purchased from Esquel Textile Co., Ltd., and the nano titanium dioxide model used was T5, which was purchased from Beijing Dekedaojin Technology Co., Ltd. Example 1
[0021] A method for preparing a washable and wrinkle-resistant fabric, comprising the following steps: (1) The cotton fabric was immersed in a 0.2wt% sodium dodecyl sulfate aqueous solution and subjected to ultrasound for 10 min. The ultrasonic frequency was 40kHz. The warp and weft density of the cotton fabric was 150*100 strands / 10cm and the surface density was 108g / cm 2 , then immersed in anhydrous ethanol for 10 minutes, the ultrasonic frequency is 40kHz, washed with pure water 4 times, and dried in a 90°C oven for 2 hours to obtain a pretreated cotton fabric; the pretreated cotton fabric is immersed in a phosphite solution for 20 minutes, wherein the phosphite solution is a mixture of phosphite and anhydrous ethanol, the mass ratio of phosphite to anhydrous ethanol is 1:12, the wet weight is controlled to be 198% after rolling, heated at 180°C for 5 minutes, and washed with pure water. , dried at 100°C for 2h, and then immersed in a 4-amino-3-nitrobenzyl alcohol solution for 20min, wherein the 4-amino-3-nitrobenzyl alcohol solution is a mixture of 4-amino-3-nitrobenzyl alcohol and anhydrous ethanol, the mass ratio of 4-amino-3-nitrobenzyl alcohol to anhydrous ethanol is 1:7, and the wet weight is controlled to be 198% after rolling, heated at 180°C for 5min, washed with pure water 4 times, and dried at 100°C for 2h to obtain a modified cotton fabric; (2) Chitosan and acetic acid aqueous solution were mixed in a mass ratio of 1:4, the volume ratio of acetic acid to pure water in the acetic acid aqueous solution was 1:30, nano-titanium dioxide was added in an amount 20 times the mass of the chitosan solution, ultrasonicated at 40kHz for 40min, 20wt% ammonia water was added in an amount 0.5 times the mass of the acetic acid aqueous solution, allowed to stand for 40min, filtered and washed with pure water for 8 times, and dried at 60°C for 3h to obtain chitosan-coated nano-titanium dioxide; chitosan-coated nano-titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:50, ultrasonicated at 40kHz for 20min, p-hydroxybenzaldehyde was added in an amount 2 times the mass of the chitosan-coated nano-titanium dioxide, the pH was adjusted to 4 with a 0.5mol / L sodium hydroxide aqueous solution, the temperature was raised to 80°C, stirred and refluxed for 4h, filtered and washed with anhydrous ethanol for 4 times, and dried at 60°C for 8h to obtain functionalized nano-titanium dioxide; (3) The modified cotton fabric was immersed in a 6wt% hydrochloric acid aqueous solution for 20 minutes, and the wet weight was controlled to be 120% after rolling. It was reacted at 30°C for 20 minutes, washed with anhydrous ethanol for 4 times, dried at 60°C for 8 hours, and then immersed in a 0.5g / mL sodium nitrite aqueous solution for 15 minutes. After rolling, the wet weight was controlled to be 90%-110%, washed with pure water for 5 times, and dried at 100°C for 2 hours to obtain a diazotized cotton fabric; (4) Modified nano titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:50, ultrasonicated at 40 kHz for 20 min, 13 wt% sodium carbonate aqueous solution was added to adjust the pH to 9, diazotized cotton fabric was added for immersion, wet weight was controlled to 60% after rolling, reacted at 30°C for 1 h, washed with pure water 4 times, dried at 100°C for 1 h, and immersed in sodium hydroxide ethanol solution for 10 min, wherein the sodium hydroxide ethanol solution is a mixture of sodium hydroxide, pure water and anhydrous ethanol. The mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5, the wet weight is controlled to be 100% after rolling, the reaction is carried out at 60°C for 30 minutes, the surface is washed with pure water for 4 times, and the surface is dried at 100°C for 2 hours, and then immersed in a glucose solution, wherein the glucose solution is a mixture of glucose and pure water, the mass ratio of glucose to pure water is 1:2.5, the wet weight is controlled to be 110% after rolling, the reaction is carried out at 60°C for 30 minutes, the surface is washed with pure water for 5 times, and the surface is dried at 100°C for 2 hours to obtain a grey cloth; (5) 1-chloromethyl-3-trifluoromethyl was prepared into a 60 g / L finishing agent solution with anhydrous ethanol, and triethylamine (0.2 times the mass of 1-chloromethyl-3-trifluoromethyl) was added, and then added to the grey fabric, wherein the mass ratio of the grey fabric to the finishing solution was 1:20. After immersion for 90 min, the fabric was subjected to a one-immersion and one-rolling process, wherein the immersion and rolling temperature was 50 °C, the rolling rate was 120%, and the fabric was pre-baked at 80 °C for 2 min, then heated to 180 °C, and baked for 5 min to obtain a washable and wrinkle-resistant fabric. Example 2
[0022] A method for preparing a washable and wrinkle-resistant fabric, comprising the following steps: (1) The cotton fabric was immersed in a 0.2wt% sodium dodecyl sulfate aqueous solution and subjected to ultrasound for 8 min. The ultrasonic frequency was 30kHz. The warp and weft density of the cotton fabric was 150*100 strands / 10cm and the surface density was 108g / cm 2 , and then immersed in anhydrous ethanol for 8 minutes with an ultrasonic frequency of 30kHz, washed with pure water 3 times, and dried in an oven at 85°C for 1.5 hours to obtain a pretreated cotton fabric; the pretreated cotton fabric was immersed in a phosphite solution for 17 minutes, wherein the phosphite solution was mixed with phosphite and anhydrous ethanol, the mass ratio of phosphite to anhydrous ethanol was 1:13, and the wet weight was controlled to be 200% after rolling, heated at 180°C for 5 minutes, washed with pure water, and The fabric was dried at 100°C for 1.5 hours, immersed in a 4-amino-3-nitrobenzyl alcohol solution for 17 minutes, wherein the 4-amino-3-nitrobenzyl alcohol solution was prepared by mixing 4-amino-3-nitrobenzyl alcohol and anhydrous ethanol, and the mass ratio of 4-amino-3-nitrobenzyl alcohol to anhydrous ethanol was 1:7.5. The wet weight was controlled to be 200% after rolling, heated at 180°C for 5 minutes, washed with pure water for 3 times, and dried at 100°C for 1.5 hours to obtain a modified cotton fabric. (2) Chitosan and acetic acid aqueous solution were mixed in a mass ratio of 1:4.5, the volume ratio of acetic acid to pure water in the acetic acid aqueous solution was 1:35, nano-titanium dioxide was added in an amount 25 times the mass of the chitosan solution, ultrasonicated at 30 kHz for 35 min, 20 wt% ammonia water was added in an amount 0.5 times the mass of the acetic acid aqueous solution, allowed to stand for 35 min, filtered and washed with pure water for 7 times, and dried at 60 °C for 2.5 h to obtain chitosan-coated nano-titanium dioxide; chitosan-coated nano-titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:55, ultrasonicated at 30 kHz for 15 min, p-hydroxybenzaldehyde was added in an amount 2.5 times the mass of the chitosan-coated nano-titanium dioxide, the pH was adjusted to 4.5 with a 0.5 mol / L sodium hydroxide aqueous solution, the temperature was raised to 70 °C, stirred and refluxed for 3.5 h, filtered and washed with anhydrous ethanol for 3 times, and dried at 60 °C for 7 h to obtain functionalized nano-titanium dioxide; (3) The modified cotton fabric was immersed in a 6wt% hydrochloric acid aqueous solution for 15 minutes, and the wet weight was controlled to be 130% after rolling. It was reacted at 28°C for 15 minutes, washed with anhydrous ethanol for 3 times, dried at 60°C for 7 hours, and then immersed in a 0.5g / mL sodium nitrite aqueous solution for 12 minutes. After rolling, the wet weight was controlled to be 100%, washed with pure water for 4 times, and dried at 100°C for 1.5 hours to obtain a diazotized cotton fabric; (4) Modified nano titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:55, ultrasonicated at 30 kHz for 15 min, 13 wt% sodium carbonate aqueous solution was added to adjust the pH to 8.5, diazotized cotton fabric was added for immersion, wet weight was controlled to 70% after rolling, reacted at 27°C for 1.5 h, washed with pure water 4 times, dried at 100°C for 1.5 h, and immersed in sodium hydroxide ethanol solution for 7 min, wherein the sodium hydroxide ethanol solution is a mixture of sodium hydroxide, pure water and anhydrous ethanol. The mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5, the wet weight is controlled to be 110% after rolling, the reaction is carried out at 55°C for 25 minutes, the surface is washed with pure water for 4 times, and the surface is dried at 100°C for 1.5 hours, and then immersed in a glucose solution, wherein the glucose solution is a mixture of glucose and pure water, and the mass ratio of glucose to pure water is 1:2.7. The wet weight is controlled to be 115% after rolling, the reaction is carried out at 55°C for 25 minutes, the surface is washed with pure water for 4 times, and the surface is dried at 100°C for 1.5 hours to obtain a grey cloth; (5) 1-chloromethyl-3-trifluoromethyl was prepared into a finishing agent solution of 70 g / L with anhydrous ethanol, and triethylamine (0.25 times the mass of 1-chloromethyl-3-trifluoromethyl) was added, and the solution was added to the grey fabric, wherein the mass ratio of the grey fabric to the finishing solution was 1:25. After immersion for 70 min, the solution was subjected to a dipping and rolling process, wherein the dipping and rolling temperature was 30 °C, the rolling rate was 110%, and the solution was pre-baked at 70 °C for 2 min, then heated to 170 °C, and baked for 3 min to obtain the fabric. Example 3
[0023] A method for preparing a washable and wrinkle-resistant fabric, comprising the following steps: (1) The cotton fabric was immersed in a 0.2wt% sodium dodecyl sulfate aqueous solution and subjected to ultrasound for 5 min. The ultrasound frequency was 20kHz. The warp and weft density of the cotton fabric was 150*100 strands / 10cm and the surface density was 108g / cm 2, then immersed in anhydrous ethanol for 5 minutes of ultrasound, the ultrasonic frequency is 20kHz, washed with pure water 3 times, and dried in an oven at 80°C for 1 hour to obtain a pretreated cotton fabric; the pretreated cotton fabric is immersed in a phosphite solution for 15 minutes, wherein the phosphite solution is a mixture of phosphite and anhydrous ethanol, the mass ratio of phosphite to anhydrous ethanol is 1:15, and the wet weight is controlled to be 202% after rolling, heated at 180°C for 5 minutes, washed with pure water, dried at 100°C for 1 hour, and then immersed in a 4-amino-3-nitrobenzyl alcohol solution for 15 minutes, wherein the 4-amino-3-nitrobenzyl alcohol solution is a mixture of 4-amino-3-nitrobenzyl alcohol and anhydrous ethanol, the mass ratio of 4-amino-3-nitrobenzyl alcohol to anhydrous ethanol is 1:8, the wet weight is controlled to be 202% after rolling, heated at 180°C for 5 minutes, washed with pure water 3 times, and dried at 100°C for 1 hour to obtain a modified cotton fabric; (2) Chitosan and acetic acid aqueous solution were mixed in a mass ratio of 1:5, the volume ratio of acetic acid to pure water in the acetic acid aqueous solution was 1:40, 30 times the mass of nano-titanium dioxide of the chitosan solution was added, ultrasonicated at 20kHz for 30min, 0.5 times the mass of 20wt% ammonia water of the acetic acid aqueous solution was added, the mixture was allowed to stand for 30min, filtered and washed with pure water for 6 times, and dried at 60℃ for 2h to obtain chitosan-coated nano-titanium dioxide; chitosan-coated nano-titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:60, ultrasonicated at 20kHz for 10min, 3 times the mass of p-hydroxybenzaldehyde of the chitosan-coated nano-titanium dioxide was added, the pH was adjusted to 4 with 0.5mol / L sodium hydroxide aqueous solution, the mixture was heated to 60℃, stirred and refluxed for 4h, filtered and washed with anhydrous ethanol for 3 times, and dried at 60℃ for 6h to obtain functionalized nano-titanium dioxide; (3) The modified cotton fabric was immersed in a 6wt% hydrochloric acid aqueous solution for 10 min, and the wet weight was controlled to be 140% after rolling. It was reacted at 25°C for 10 min, washed with anhydrous ethanol for 3 times, dried at 60°C for 6 h, and then immersed in a 0.5g / mL sodium nitrite aqueous solution for 10 min. After rolling, the wet weight was controlled to be 110%, washed with pure water for 4 times, and dried at 100°C for 1 h to obtain a diazotized cotton fabric. (4) Modified nano titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:60, ultrasonicated at 20 kHz for 10 min, 13 wt% sodium carbonate aqueous solution was added to adjust the pH to 8, diazotized cotton fabric was added for immersion, wet weight was controlled to 80% after rolling, reacted at 25°C for 1 h, washed with pure water, dried at 100°C for 1 h, and immersed in sodium hydroxide ethanol solution for 5 min, wherein the sodium hydroxide ethanol solution is a mixture of sodium hydroxide, pure water and anhydrous ethanol. The mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5, the wet weight is controlled to be 120% after rolling, the reaction is carried out at 50°C for 20 minutes, the cloth is washed with pure water 4 times, and dried at 100°C for 1 hour, and then immersed in a glucose solution, wherein the glucose solution is a mixture of glucose and pure water, the mass ratio of glucose to pure water is 1:3, the wet weight is controlled to be 120% after rolling, the cloth is reacted at 50°C for 20 minutes, the cloth is washed with pure water 4 times, and dried at 100°C for 1 hour to obtain a grey cloth; (5) 1-chloromethyl-3-trifluoromethyl was prepared into a finishing agent solution of 80 g / L with anhydrous ethanol, and triethylamine (0.3 times the mass of 1-chloromethyl-3-trifluoromethyl) was added, and the solution was added to the grey fabric, wherein the mass ratio of the grey fabric to the finishing solution was 1:30. After immersion for 60 min, the solution was subjected to a dipping and rolling process, wherein the dipping and rolling temperature was 20 °C, the rolling rate was 120%, and the solution was pre-baked at 60 °C for 2 min, then heated to 150 °C, and baked for 2 min to obtain a washable and wrinkle-resistant fabric.
[0024] Comparative Example 1 The preparation method of the washable and wrinkle-resistant fabric of Comparative Example 1 is different from that of Example (2) in that step (1) is modified to immerse the cotton fabric in a 0.2wt% sodium dodecyl sulfate aqueous solution and ultrasonicate for 8 min, the ultrasonic frequency is 30kHz, the warp and weft density of the cotton fabric is 150*100 strands / 10cm, and the surface density is 108g / cm 2 , then immersed in anhydrous ethanol for 8 minutes, the ultrasonic frequency is 30kHz, washed with pure water 3 times, and dried in an oven at 85°C for 1.5 hours to obtain a pretreated cotton fabric; the pretreated cotton fabric was immersed in a phosphite solution for 17 minutes, wherein the phosphite solution is a mixture of phosphite and anhydrous ethanol, the mass ratio of phosphite to anhydrous ethanol is 1:13, and the wet weight is controlled to be 200% after rolling, heated at 180°C for 5 minutes, washed with pure water, and dried at 100°C for 1.5 hours to obtain a modified cotton fabric; Comparative Example 2 The preparation method of the washable and wrinkle-resistant fabric of Comparative Example 2 differs from that of Example (2) in that step (2) is not included, and step (4) is modified to ultrasonicate anhydrous ethanol at 30 kHz for 15 min, add 13 wt % sodium carbonate aqueous solution to adjust the pH to 8.5, add diazotized cotton fabric for immersion, control the wet weight to 70% after rolling, react at 27° C. for 1.5 h, wash with pure water 4 times, dry at 100° C. for 1.5 h, and immerse in sodium hydroxide ethanol solution for 7 min, wherein the sodium hydroxide ethanol solution is composed of sodium hydroxide, pure water and anhydrous ethanol, wherein the mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5, the wet weight is controlled to be 110% after rolling, react at 55°C for 25min, wash with pure water 4 times, dry at 100°C for 1.5h, and then immerse in a glucose solution, wherein the glucose solution is mixed with glucose and pure water, the mass ratio of glucose to pure water is 1:2.7, the wet weight is controlled to be 115% after rolling, react at 55°C for 25min, wash with pure water 4 times, and dry at 100°C for 1.5h to obtain a grey cloth; Comparative Example 3 The preparation method of the washable and wrinkle-resistant fabric of Comparative Example 3 differs from that of Example (2) in that step (5) is not included, and step (4) is modified as follows: modified nano titanium dioxide and anhydrous ethanol are mixed in a mass ratio of 1:55, ultrasonicated at 30 kHz for 15 minutes, 13 wt % sodium carbonate aqueous solution is added to adjust the pH to 8.5, diazotized cotton fabric is added for immersion, wet weight is controlled to be 70% after rolling, reacted at 27° C. for 1.5 hours, washed with pure water 4 times, dried at 100° C. for 1.5 hours, and then immersed in a sodium hydroxide ethanol solution for 7 minutes, wherein the sodium hydroxide ethanol solution It is made of a mixture of sodium hydroxide, pure water and anhydrous ethanol, wherein the mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5, and the wet weight is controlled to be 110% after rolling. It is reacted at 55°C for 25 minutes, washed with pure water for 4 times, dried at 100°C for 1.5 hours, and then immersed in a glucose solution, wherein the glucose solution is made of a mixture of glucose and pure water, and the mass ratio of glucose to pure water is 1:2.7. The wet weight is controlled to be 115% after rolling, and it is reacted at 55°C for 25 minutes, washed with pure water for 4 times, and dried at 100°C for 1.5 hours to obtain a washable and wrinkle-resistant fabric.
[0025] Test Example 1 Flame retardant performance test Test method: The limiting oxygen index of the examples and comparative examples was tested using the intelligent oxygen index determination according to the standard GB / T 5454-1997 “Oxygen index method for burning performance of textiles”. The results are shown in Table 1.
[0026] Table 1
[0027] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be found that the washable and wrinkle-resistant fabric prepared by the present invention has good flame retardant properties.
[0028] By comparison, the limiting oxygen index of Examples 1-3 is greater than that of Comparative Example 3, indicating that the pretreated cotton fabric, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol are reacted to obtain a modified cotton fabric, the pretreated cotton fabric and triethyl phosphite are subjected to an ester exchange reaction, and a structure having flame retardant properties is grafted on the cotton fabric to give the fabric flame retardant properties, and finally 1-chloromethyl-3-trifluoromethylbenzene is used, and the introduction of fluoromethyl can also further improve the flame retardant properties of the fabric.
[0029] Test Example 2 UV resistance test Test method: The washable and wrinkle-resistant fabrics prepared in each embodiment and comparative example were tested for transmittance using an Agilent Cary5000 UV-visible-near infrared spectrophotometer according to the standard "AS / NZS 4399:1996". The fabric size was cut into 10 cm×10 cm. The results are shown in Table 2.
[0030] Washability test Test method: After washing and drying the washable and wrinkle-resistant fabrics prepared in all comparative examples and embodiments for 10 times according to the standard AATCC TM124-2009 "Appearance smoothness of fabrics after multiple home washings", the transmittance of the fabrics was tested according to the test method for anti-ultraviolet performance. The results are shown in Table 2.
[0031] Table 2
[0032] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 2, it can be found that the washable and wrinkle-resistant fabric prepared by the present invention has good UV resistance and washability.
[0033] By comparing the transmittance of Examples 1-3, which is less than that of Comparative Examples 1-2, it is shown that nano-titanium dioxide has a high refractive index and can not only reflect ultraviolet rays but also absorb ultraviolet rays, which can give the fabric good anti-ultraviolet performance. The amino group on chitosan can form a Schiff base with the aldehyde group on p-hydroxybenzaldehyde to introduce a phenolic hydroxyl structure on the surface of nano-titanium dioxide, which can be used for subsequent reactions; the modified cotton fabric and the modified nano-titanium dioxide are reacted to obtain a modified cotton grey cloth, and then 1-chloromethyl-3-trifluoromethylbenzene is used for post-finishing to obtain a washable and wrinkle-resistant fabric; the nitroaniline structure on the modified cotton fabric is diazotized to form a salt, which can be coupled with the phenolic hydroxyl structure on the surface of the nano-titanium dioxide, and then reduced by glucose to finally form a benzotriazole structure, which is based on the phenolic-quinone tautomer that converts the absorbed light energy into heat energy to achieve the effect of absorbing ultraviolet rays and further improve the anti-ultraviolet performance of the fabric; after washing, the transmittance of Comparative Examples 1 and 2 decreases significantly, indicating that the components are cross-linked by covalent bonds, and the fabric has good washability.
[0034] Test Example 3 Anti-wrinkle performance test Test method: The washable and wrinkle-resistant fabrics prepared in each embodiment and comparative example were tested for recovery angle on a YG541L digital fabric wrinkle elasticity tester according to the standard GB / T3819-1997 "Recovery angle method for determination of crease recovery of textile fabrics". The results are shown in Table 3.
[0035] Table 3
[0036] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 3, it can be found that the washable and wrinkle-resistant fabric prepared by the present invention has good wrinkle-resistant performance.
[0037] By comparing the recovery angle of Example 1-3, which is greater than the recovery angle of Comparative Example 1-2, it is explained that when preparing the washable and wrinkle-resistant fabric of the present invention, the pretreated cotton fabric, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol are first reacted to obtain a modified cotton fabric, and then the chitosan-wrapped nano titanium dioxide is reacted with p-hydroxybenzaldehyde to obtain a modified nano titanium dioxide, and then the modified cotton fabric and the modified nano titanium dioxide are reacted to obtain a modified cotton grey cloth, and then 1-chloromethyl-3-trifluoromethylbenzene is used for post-finishing, and each component is directly connected by a covalent bond. Finally, 1-chloromethyl-3-trifluoromethylbenzene is used for finishing to react with the excess phenolic hydroxyl structure on the surface of the nano titanium dioxide, thereby reducing the excess active groups on the surface of the fabric and improving the wrinkle-resistant performance of the fabric.
[0038] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A washable and wrinkle-resistant fabric, characterized in that: The washable and wrinkle-resistant fabric is prepared by reacting modified cotton fabric with modified nano-titanium dioxide to obtain modified cotton grey fabric, and then post-finishing with 1-chloromethyl-3-trifluoromethylbenzene; The modified cotton fabric is prepared by reacting pretreated cotton fabric, triethyl phosphite and 4-amino-3-nitrobenzyl alcohol; The modified nano titanium dioxide is prepared by reacting nano titanium dioxide wrapped by chitosan with p-hydroxybenzaldehyde.
2. A method for preparing a washable and wrinkle-resistant fabric, characterized in that: The method comprises the following preparation steps: (1) The pretreated cotton fabric is immersed in a phosphite solution for 15-20 minutes, and the wet weight is controlled to be 198%-202% after rolling, and heated at 180°C for 5 minutes, washed with pure water, and dried at 100°C for 1-2 hours, and then immersed in a 4-amino-3-nitrobenzyl alcohol solution for 15-20 minutes, and the wet weight is controlled to be 198%-202% after rolling, and heated at 180°C for 5 minutes, and washed with pure water 3-4 times, and dried at 100°C for 1-2 hours to obtain a modified cotton fabric; (2) Mix the chitosan-coated nano-titanium dioxide and anhydrous ethanol at a mass ratio of 1:50-60, ultrasonicate at 20-40kHz for 10-20min, add p-hydroxybenzaldehyde 2-3 times the mass of the chitosan-coated nano-titanium dioxide, adjust the pH to 4-5 with a 0.5mol / L sodium hydroxide aqueous solution, heat to 60-80°C, stir and reflux for 3-4h, filter and wash with anhydrous ethanol for 3-4 times, and dry at 60°C for 6-8h to obtain functionalized nano-titanium dioxide; (3) The modified cotton fabric is immersed in a 6wt% hydrochloric acid aqueous solution for 10-20 minutes, and the wet weight is controlled to be 120%-140% after rolling. The fabric is reacted at 25-30°C for 10-20 minutes, washed with anhydrous ethanol for 3-4 times, dried at 60°C for 6-8 hours, and then immersed in a 0.5g / mL sodium nitrite aqueous solution for 10-15 minutes. The wet weight is controlled to be 90%-110% after rolling, washed with pure water for 4-5 times, and dried at 100°C for 1-2 hours to obtain a diazotized cotton fabric; (4) Modified nano titanium dioxide and anhydrous ethanol were mixed in a mass ratio of 1:50-60, ultrasonicated at 20-40kHz for 10-20min, 13wt% sodium carbonate aqueous solution was added to adjust the pH to 8-9, diazotized cotton fabric was added for immersion, wet weight was controlled to 60%-80% after rolling, reacted at 25-30℃ for 1-2h, washed with pure water for 4-5 times, dried at 100℃ for 1-2h, and then immersed in sodium hydroxide. 5-10 minutes in ethanol solution, after rolling, the wet weight is controlled to be 100%-120%, reacted at 50-60°C for 20-30 minutes, washed with pure water for 4-5 times, dried at 100°C for 1-2 hours, immersed in glucose solution, after rolling, the wet weight is controlled to be 110%-120%, reacted at 50-60°C for 20-30 minutes, washed with pure water for 4-5 times, dried at 100°C for 1-2 hours, and obtained grey cloth; (5) 1-chloromethyl-3-trifluoromethyl is prepared into a finishing agent solution of 60-80 g / L with anhydrous ethanol, triethylamine is added in an amount of 0.2-0.3 times the mass of 1-chloromethyl-3-trifluoromethyl, and the solution is added to the grey fabric, wherein the mass ratio of the grey fabric to the finishing solution is 1:20-30. After immersion for 60-90 min, the solution is subjected to a one-immersion-one-rolling process, pre-baked at 60-80°C for 2 min, and then heated to 150-180°C and baked for 2-5 min to obtain a washable and wrinkle-resistant fabric.
3. The method for preparing a washable and wrinkle-resistant fabric according to claim 2, characterized in that: The preparation method of the pretreated cotton fabric in step (1) is as follows: immersing the cotton fabric in a 0.2wt% sodium dodecyl sulfate aqueous solution and ultrasonicating for 5-10 minutes, the ultrasonic frequency is 20-40kHz, the warp and weft density of the cotton fabric is 150*100 strands / 10cm, and the surface density is 108g / cm 2 , then immersed in anhydrous ethanol for 5-10 minutes, the ultrasonic frequency is 20-40kHz, washed with pure water for 3-4 times, and dried in an oven at 80-90℃ for 1-2h to obtain the pretreated cotton fabric.
4. The method for preparing a washable and wrinkle-resistant fabric according to claim 2, characterized in that: The phosphite solution in step (1) is prepared by mixing phosphite and anhydrous ethanol, wherein the mass ratio of phosphite to anhydrous ethanol is 1:12-15; the 4-amino-3-nitrobenzyl alcohol solution is prepared by mixing 4-amino-3-nitrobenzyl alcohol and anhydrous ethanol, wherein the mass ratio of 4-amino-3-nitrobenzyl alcohol to anhydrous ethanol is 1:7-8.
5. The method for preparing a washable and wrinkle-resistant fabric according to claim 2, characterized in that: The preparation method of the chitosan-coated nano-titanium dioxide in step (2) is as follows: chitosan and acetic acid aqueous solution are uniformly mixed in a mass ratio of 1:4-5, wherein the volume ratio of acetic acid to pure water in the acetic acid aqueous solution is 1:30-40, nano-titanium dioxide is added in an amount 20-30 times the mass of the chitosan solution, ultrasonicated at 20-40 kHz for 30-40 min, 20wt% ammonia water is added in an amount 0.5 times the mass of the acetic acid aqueous solution, the mixture is allowed to stand for 30-40 min, filtered and washed with pure water for 6-8 times, and dried at 60° C. for 2-3 h to obtain chitosan-coated nano-titanium dioxide.
6. The method for preparing a washable and wrinkle-resistant fabric according to claim 2, characterized in that: The sodium hydroxide ethanol solution in step (4) is prepared by mixing sodium hydroxide, pure water and anhydrous ethanol, wherein the mass ratio of sodium hydroxide, pure water and anhydrous ethanol is 1:5:5; the glucose solution is prepared by mixing glucose and pure water, wherein the mass ratio of glucose to pure water is 1:2.5-3.
7. The method for preparing a washable and wrinkle-resistant fabric according to claim 2, characterized in that: The one-immersion-one-rolling process in step (5) is as follows: the immersion-rolling temperature is 20-50° C., and the rolling rate is 100%-120%.
8. The method for preparing a washable and wrinkle-resistant fabric according to claim 5, characterized in that: The nano titanium dioxide model is T5.
Citation Information
Cited By
Cotton fabric anti-ultraviolet anti-wrinkle finishing agent and preparation method thereof
CN121719079A
An ultraviolet resistant and wrinkle resistant finishing agent for cotton fabric and a preparation method thereof
CN121719079B
